Implementasi Asas Kepentingan Umum dalam Mewujudkan Kesejahteraan Rakyat : Studi Disdukcapil Kabupaten Bekasi - Suwanti, Robet; Sinaga, Parbuntian; Bhakti, Teguh Satya (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the implementation of the principle of public interest in the implementation of public services by the Population and Civil Registration Office (Disdukcapil) of Bekasi Regency, as well as to evaluate the extent to which the implementation of these principles contributes to efforts to realize people's welfare. The principle of public interest is one of the basic principles in the implementation of public services that emphasizes the fulfillment of basic rights of the community in a fair, fast, equitable, and accountable manner. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews, direct observations in the field, and documentation studies on various policies and service reports. The results of the study show that the Bekasi Regency Disdukcapil has adopted various innovations in services, such as online services, digital queue systems, the use of information technology-based applications, and increasing the transparency of service information through social media and official websites. These steps are taken to improve accessibility, efficiency, effectiveness, and community satisfaction as service recipients. However, the implementation of the principle of public interest still faces several obstacles, such as limited competent human resources (HR), uneven information technology infrastructure, and low digital literacy among certain communities, especially the elderly and people in suburban areas. This condition results in the suboptimal public service oriented to the public interest to the maximum. Therefore, continuous efforts are needed through increasing the capacity of the apparatus, the development of inclusive and adaptive public service technology, and massive education to the public to increase participation, understanding, and awareness of the available services. Thus, the public services that are carried out can really contribute to realizing the welfare of the people as a whole, equitable, and just.